Enhancing Recoverable Bendability of Ag2Te‐Based Thermoelectrics by Elastic Strain Manipulation - Zimin Fan; Wenjun Ding; Xinyi Shen; Jun Luo; Wen Li; Yanzhong Pei (Advanced Electronic Materials)
Abstract Inherent rigidity of high‐performing inorganic thermoelectric materials constrains their potential applications as flexible power sources for the wearable electronics. Deformation within the elastic region ensures the reservation of a material's initial functionalities, motivating the current work to focus on the elasticity enhancement of Ag2Te thermoelectric. Ag2S‐alloying results in an observable reduction in the modulus of Ag2Te1‐xSx alloys (x ≤ 0.3), which thereby enables not only a great increase in the elastic strain but also a significant plasticization of the alloys, allowing the plastic deformability by the rolling at a temperature of ≈120 °C. Such a plastic deformation‐induced improvement in yield strength leads to a further improvement of the elastic strain up to 1.8%, corresponding to ≈200% enhancements as compared to pristine Ag2Te (≈0.6%). Eventually, the multi‐pass hot‐rolled Ag2Te0.9S0.1 film achieves a full recoverability in transport properties even after elastic bending within a tiny radius of ≈3 mm for 100 000 times and a power density as high as ≈25 W m−2 in six‐leg device. This work robustly demonstrates a universal strategy to advance the recoverable bendability of inorganic thermoelectric materials for flexible applications.